TRES ESPECIES NUEVAS DE AEDES DIPTERA CULICIDAE - VARGAS, LUIS; DOWNS WILBUR, G (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
A (Ochlerotatus) shannoni, A (Gualteria) ramirezi and A (G) kompi, all from Morelos, Mexico The larvae, pupae, and adults, including male genitalia, are descr
REV SOC MEX HIST NAT
Keywords: ESPECIES NUEVAS, AEDES DIPTERA CULICIDAE; CIENCIAS DE LA VIDA; BIOLOGIA DE LOS INSECTOS (ENTOMOLOGIA); MORFOLOGIA DE LOS INSECTOS